Enhancing the Creative Economy of MSMEs in Villages via Business Digitalization: KKN involvement Campaign in Serdang Wetan Village - Nasution, Atiqi Chollisni; Rosita; Wulandari, Fithri; Alfiah; Amanda; Kholifah, Nur; Rahayu, Pipih; Fauziah, Delia Isna; Sabrina, Meriana Khalifah (Research and Social Study Institute, 2026)
Background: The Community Service Program (PKM) will be implemented through Student Community Service Program Course (KKN) in July-August 2025 in Serdang Wetan local, Legok District, Tangerang Regency, with the objective of enhancing the competitiveness of local MSMEs by strengthening the creative economy through the digitization of business. MSME partners predominantly face challenges like insufficient company legitimacy, limited product branding expertise, inadequate digital and financial literacy, and a lack of knowledge in electronic payment technology and digital promotional methods.Aims: Enhancing the creative economy of MSMEs in Serdang Wetan village via business digitalization.Methods: The PKM implementation method utilizes a